A review of T-stress and its effects in fracture mechanics. (January 2015) - Gupta, M.; Alderliesten, R.C.; Benedictus, R.
Highlights: Review on T -stress. T -stress effects in fracture mechanics. T -stress' role as constraint parameter. T -stress does not predict crack path stability accurately and reliably. Abstract: An overview of past research on T -stress is presented in this paper. Beginning with the origin of T -stress, the authors discuss different phenomena associated with T -stress: crack path stability, isochromatic fringes pattern, plastic zone influence and constraint parameter. Different methodologies—experimental, analytical and finite element methods—used to evaluate T -stress are discussed and studies are categorized under these methods also. Thereafter, the authors provide a critical review for the role of T -stress in predicting crack paths stability because it conflicts with the origin of T -stress. Finally, it concludes with a concise summary of the research on T -stress.